(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Without detracting from the advantages of traditional echinococcectomies, we believe that the approach to choosing a surgical method should be strictly differentiated. Echinococcal cysts with a diameter of more than 50 mm, as well as recurrent cysts complicated by suppuration, as we gain experience, we allowed ourselves to interpret as “relative” contraindications to videothoracoscopic echinococcectomy of the lung; in the treatment of pulmonary echinococcosis, endovideosurgical echinococcectomy is and should be a priority.